Mississippi currents journeys through time and a valley - Malcolm, Andrew H.; Straus, Roger (New York : William Morrow and Co., 1996)
Andrew H. Malcolm and Roger Straus III tell in evocative words and eloquent pictures the story of the Mississippi and the Americans who live, love, work, and play along its length. We meet hard-hatted riverboat crew women, Tom Sawyer wannabes, a new breed of riverboat gamblers, elderly riverbank philosophers, and ferry pilots who have seen the river - and the people along it - change drastically over the years. We learn the thoughts of the ranger who lives in the.; Minnesota woods by the little lake that is the Mississippi's long-hidden true source, and talk to the aging mayor of a Louisiana delta town abandoned by all living residents - except on election day. Through these and other intriguing stories, and more than sixty stunning photographs, Malcolm and Straus portray the countless ways the Mississippi has shaped the lives, economy, literature, and indeed, the entire character of the American Heartland.
76865
Keywords: Mississippi River -- Description and travel; Mississippi River -- Pictorial works; Mississippi River Valley -- Description and travel; Mississippi River Valley -- Pictorial works